Letter from Carl D. Duncan to Patricia Whiting, June 27, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan expresses his admiration for Whiting's family and comments on the healing power of positive suggestion, hoping that it will relieve him of a taxing routine of medications.